Axisymmetry in Mechanical Engineering - Willert, Emanuel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint is devoted to the phenomena associated with exact or approximate axial symmetry in different areas of technical physics and mechanical engineering science. How can the symmetry of the problem be used most efficiently for its analysis? Why is the symmetry broken or why is it still approximately retained? These and other questions are discussed based on systems from different fields of engineering.